A continuous metallurgical compounding method for Ag / In2O3 / Cu composite strip based on semi-solid interface regulation

CN122974875APending Publication Date: 2026-10-27KUNMING UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610982143.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-02
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

然而,此类过渡层主要依赖机械附着或表面粘结作用,在连续化高温复合过程中容易发生界面漂移、颗粒偏聚或局部脱落等现象,导致过渡层难以长期稳定存在,其界面调控作用难以充分发挥,从而影响复合材料界面结构的稳定性

Benefits of technology

1. 本发明利用半固态铜带液固共存界面的高界面活性、界面润湿特性及液相包覆能力等特点,实现In2O3颗粒的原位稳定嵌入固定,形成高稳定性的含In2O3颗粒界面过渡层,促进界面过渡层充分发挥作用,改善Ag液在Cu基体表面的润湿与铺展能力,促进Ag层与Cu基体之间形成连续冶金结合界面。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122974875A_ABST
    Figure CN122974875A_ABST
Patent Text Reader

Abstract

The application discloses a kind of Ag / In2O3 / Cu composite strip continuous metallurgical composite methods based on semi-solid interface regulation, belong to silver-based electric contact composite material and continuous metallurgical composite forming technical field.The present application includes S1: continuously casting to copper molten liquid, obtain the semi-solid copper strip with liquid-solid coexistence state in surface layer;S2: In2O3 Granules are scattered in the surface layer of semi-solid copper strip with liquid-solid coexistence state, form interface transition layer containing In2O3 Granules;S3: silver molten liquid is cast on interface transition layer, obtain composite strip blank;S4: composite strip blank is carried out multi-pass hot rolling and annealing treatment cycle, obtain Ag / In2O3 / Cu composite strip.The present application is by In2O3 Granules is added to the surface of semi-solid copper strip, utilizes the support coating synergistic effect of liquid-solid coexistence interface to realize particle in-situ embedding, constructs stable interface transition layer and cooperates silver liquid continuous casting and hot rolling plastic densification processing, by the process of high continuity high efficiency production interface bonding stability, organization dense and stable Ag / In2O3 / Cu composite strip of electric conduction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of silver-based electrical contact composite materials and continuous metallurgical composite forming technology, and relates to a continuous metallurgical composite method for Ag / In2O3 / Cu composite strips based on semi-solid interface control. Background Technology

[0002] Silver-based electrical contact materials are widely used in low-voltage electrical appliances, relays, rail transit and new energy power transmission and distribution equipment due to their excellent electrical conductivity, thermal conductivity and anti-welding properties.

[0003] While AgCdO silver-based electrical contact materials, which are widely used, exhibit good resistance to arc erosion, Cd and its oxides are prone to environmental pollution and biotoxicity risks during production and service, making it difficult to meet the development needs of green and environmentally friendly electrical contact materials. Therefore, the development of high-performance, environmentally friendly silver-based composite electrical contact materials is of great significance.

[0004] Compared to AgCdO silver-based electrical contact materials, Ag / Cu composite tapes combine the excellent conductivity of silver layers with the low cost and high strength of copper layers, while avoiding the environmental pollution risks associated with Cd. Therefore, they have promising applications in low-voltage electrical appliances, electrical contact components, and new energy power transmission and distribution systems. However, existing Ag / Cu composite tapes and their preparation technologies still have the following shortcomings: (1) At present, Ag / Cu composite materials are mainly prepared by powder metallurgy, explosive bonding, hot-press diffusion bonding and mechanical bonding. The above processes usually have the problems of discrete production process and low degree of continuity, which is not conducive to the continuous preparation of long Ag / Cu composite strips. At the same time, due to the limitation of process conditions on the interface bonding process, there is still room for further improvement in the interface bonding quality and long-term service stability of the obtained composite materials.

[0005] (2) To improve production efficiency and continuous manufacturing capabilities, continuous metallurgical composite technology has gradually attracted attention. However, due to the large interfacial energy difference between Ag liquid and Cu matrix, the wetting and spreading behavior of Ag liquid on Cu surface is limited. In the continuous metallurgical composite process, local insufficient wetting is prone to occur, making it difficult for Ag liquid to form a uniform and continuous coverage on Cu surface, which in turn induces defects such as interfacial porosity, microcracks and local interfacial separation, affecting the electrical conductivity stability and long-term service reliability of composite strip.

[0006] (3) In the prior art, a transition layer can be constructed on the surface of Cu matrix by means of interface spraying, surface coating, etc., to improve the Ag / Cu interface bonding performance. However, such transition layers mainly rely on mechanical adhesion or surface bonding. During continuous high-temperature composite processes, phenomena such as interface drift, particle agglomeration, or local detachment are prone to occur, making it difficult for the transition layer to exist stably for a long time. Its interface regulation function is difficult to be fully utilized, thus affecting the stability of the composite material interface structure.

[0007] Therefore, there is an urgent need to develop a novel Ag / Cu composite strip preparation method that combines continuous manufacturing capability with interface stability control function. While ensuring production continuity, it is necessary to achieve stable fixation and effective control of the interface transition layer, thereby improving the wetting and spreading behavior of Ag liquid on the Cu matrix surface, enhancing the Ag / Cu interface bonding ability, and obtaining Ag / In2O3 / Cu composite strips with excellent conductivity, interface stability and service reliability. Summary of the Invention

[0008] To overcome the problems in the prior art, this invention utilizes the high interfacial activity of the liquid-solid coexistence interface of semi-solid copper strip to construct a stable and fixed In2O3-containing interfacial transition layer on the surface of the copper strip. This allows the transition layer to fully exert its effect, regulates the interfacial stability between the Ag layer and the Cu matrix, and enables continuous production of Ag / In2O3 / Cu composite strips. Ultimately, this improves the production efficiency, interfacial bonding strength, microstructure uniformity, electrical conductivity stability, and arc erosion resistance of the composite strips.

[0009] To achieve the above objectives, the present invention is implemented through the following technical solution: This invention proposes a continuous metallurgical composite method for Ag / In₂O₃ / Cu composite strips based on semi-solid interface control. The continuous metallurgical composite method for Ag / In₂O₃ / Cu composite strips includes the following steps: S1: Continuous casting of molten copper yields a semi-solid copper strip with a liquid-solid coexistence state on the surface.

[0010] S2: Spread In2O3 particles on the surface of the semi-solid copper strip in step S1, where it is in a liquid-solid coexistence state. Under the action of capillary force and interfacial tension at the liquid-solid coexistence interface, the In2O3 particles are embedded in situ into the surface of the semi-solid copper strip, forming an interfacial transition layer containing In2O3 particles.

[0011] S3: The molten silver is poured onto the interface transition layer of step S2 to obtain a composite strip blank.

[0012] S4: Perform multiple hot rolling and annealing cycles on the composite strip blank obtained in step S3 to obtain Ag / In2O3 / Cu composite strip.

[0013] Copper molten liquid is obtained by heating and melting electrolytic copper with a purity of not less than 99.95%, and silver molten liquid is obtained by heating and melting industrial pure silver with a purity of not less than 99.95%.

[0014] Preferably, in step S1, the cooling intensity of the crystallizer during the continuous casting process is 0.5~3.0 MW / m. 2 The continuous casting traction speed is 0.5–5.0 m / min, and the cooling rate in the secondary cooling zone is 10–100 °C / s.

[0015] By controlling the cooling intensity of the crystallizer, the continuous casting traction speed, and the cooling rate of the secondary cooling zone within the above range, the solid fraction in the liquid-solid coexistence material on the surface of the semi-solid copper strip can be maintained at 20%~60%, thereby keeping the solid fraction on the surface of the liquid-solid coexistence layer within a better range. This avoids excessively high fluidity causing In2O3 particles to be displaced by the fluid, and avoids excessively low fluidity, which would prevent In2O3 particles from effectively embedding into the surface of the semi-solid copper strip.

[0016] Preferably, in step S1, the casting temperature of the molten copper is 1150~1250℃.

[0017] Preferably, in step S2, In2O3 particles are evenly distributed on the surface of the semi-solid copper strip, at a concentration of 0.01~0.50 g / cm³ based on the area of ​​the semi-solid copper strip. 2 In2O3 particles are evenly distributed on the surface of the semi-solid copper strip in a liquid-solid coexistence state.

[0018] In2O3 particles can be evenly distributed on the liquid-solid coexisting surface of the semi-solid copper strip by using a vibrating powder spreading device, an oscillating funnel, or an air jet method.

[0019] Preferably, in step S2, the In2O3 particles have a particle size of 50~800nm.

[0020] Further optimization yields In2O3 particles with a particle size of 100~600nm.

[0021] Preferably, in step S3, after the In2O3 particles are sprinkled, they travel with the semi-solid copper strip for 5-30 seconds before entering the silver molten liquid casting area to begin silver molten liquid casting.

[0022] Preferably, in step S3, the casting temperature of the molten silver is 980~1050℃.

[0023] Preferably, in step S3, the flow rate of the silver molten liquid casting is 0.05–5 kg / min.

[0024] Preferably, in step S4, the hot rolling temperature is 550–700°C, the single-pass hot rolling deformation is 5%–20%, and the total hot rolling deformation is 20%–80%; the annealing temperature is 450–650°C, and the single annealing holding time is 0.5–4 hours.

[0025] Further optimization yields a total hot-rolled deformation of 35% to 75%.

[0026] Further optimization involves setting the annealing temperature to 500~650℃ and the holding time for each annealing cycle to 1~3 hours.

[0027] Preferably, steps S1, S2, S3 and S4 are all performed under inert gas protection conditions, wherein the inert gas is argon, nitrogen or a mixture of argon and nitrogen.

[0028] When the inert gas is a mixture of argon and nitrogen, the argon and nitrogen are mixed in any proportion.

[0029] In this invention, In2O3 particles can be purchased commercially or prepared by the following methods: (1) Dissolve In(NO3)3·xH2O in deionized water to prepare an indium source solution with a concentration of 0.2mol / L~0.8mol / L, and stir at room temperature for 10min~30min.

[0030] (2) Add ammonia water to the indium source solution as a precipitant and control the pH of the system to 7~9. Under continuous stirring, the In(OH)3 precursor precipitate is generated.

[0031] (3) The obtained In(OH)3 precursor precipitate was washed with deionized water and anhydrous ethanol and dried at 60℃~100℃ for 4h~12h.

[0032] (4) Heat-treat the dried precipitate at 500℃~700℃ for 1h~3h, and obtain In2O3 particles after natural cooling.

[0033] The beneficial effects of this invention are: 1. This invention utilizes the high interfacial activity, interfacial wetting properties, and liquid phase coating ability of the semi-solid copper strip liquid-solid coexistence interface to achieve in-situ stable embedding and fixation of In2O3 particles, forming a highly stable In2O3 particle-containing interfacial transition layer. This promotes the full functioning of the interfacial transition layer, improves the wetting and spreading ability of Ag liquid on the Cu substrate surface, and promotes the formation of a continuous metallurgical bonding interface between the Ag layer and the Cu substrate.

[0034] 2. Unlike traditional interface spraying or surface coating processes, the liquid-solid coexistence surface layer of the semi-solid copper strip of this invention has both solid-phase skeleton support and liquid-phase flow coating capabilities. This allows In2O3 particles to be embedded in the copper strip surface layer under the synergistic effect of interfacial tension and capillary force to form a stable interface transition layer. Furthermore, in the interface transition layer, the In2O3 particles are distributed in a discontinuous manner, which not only improves the continuity of Ag / Cu interface bonding but also helps maintain the conductivity stability of the composite strip.

[0035] 3. This invention introduces In2O3 particles as an interfacial transition layer additive, which is beneficial to the formation tendency of interfacial porosity and local unbonded defects in the composite strip, improves the continuous metallurgical bonding stability of the Ag / Cu interface, and obtains a composite strip with better overall performance.

[0036] 4. This invention establishes a synergistic preparation process of "continuous casting—multi-pass hot rolling—annealing treatment" to achieve continuous manufacturing of Ag / In2O3 / Cu composite strip. Compared with traditional step-by-step processing, this method has tight process connections, short production cycle, and high interface bonding quality, and has good prospects for industrial application.

[0037] 5. The present invention uses multi-pass hot rolling synergistic annealing treatment, which is beneficial to further improve the density of the composite interface structure and the continuity of interface contact of the composite strip.

[0038] 6. The Ag / In2O3 / Cu composite tape prepared by this invention has excellent interfacial stability, electrical conductivity stability and anti-arc erosion performance, and can achieve highly reliable electrical connections in the fields of low-voltage electrical appliances, rail transit, and new energy power transmission and distribution.

[0039] 7. The discontinuous dispersed In2O3 interface transition layer constructed by the present invention can take into account both interface strengthening and conductivity continuity. Compared with continuous oxide isolation layer, it can effectively reduce interface resistance and improve arc erosion lifetime, achieving synergistic improvement of interface bonding strength, conductivity and ablation resistance. Attached Figure Description

[0040] Figure 1 This is a schematic diagram of the continuous metallurgical composite method for Ag / In2O3 / Cu composite strip of the present invention; Figure 2 This is a metallographic morphology diagram of the interface region of the Ag / In2O3 / Cu composite strip of the present invention. Detailed Implementation

[0041] The present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments, but the scope of protection of the present invention is not limited to the content described.

[0042] The In2O3 particles used in the embodiments and comparative examples of this invention are self-prepared products.

[0043] Example 1 This embodiment prepares Ag / In2O3 / Cu composite tape using the following method: The preparation process in this embodiment was carried out in an argon-protected environment.

[0044] (1) Electrolytic copper with a purity of 99.95% is heated to 1180℃ to form copper molten liquid. The continuous casting traction speed of the continuous casting equipment is set to 2.0m / min, the cooling intensity of the crystallizer is set to 1.8MW / m², and the cooling rate of the secondary cooling zone is set to 50℃ / s to continuously cast the copper molten liquid, and a semi-solid copper strip with a liquid-solid coexistence state on the surface is obtained. The solid phase in the surface of the semi-solid copper strip is 40%.

[0045] (2) Set the oscillation frequency of the oscillating funnel to 30 times / min. Use the oscillating funnel to evenly spread In2O3 particles with a particle size of 100~300nm on the surface of the semi-solid copper strip in a liquid-solid coexistence state. The amount of In2O3 particles added is 0.15g / cm² (0.15g of In2O3 particles are spread on each square centimeter of semi-solid copper strip). As continuous casting continues, the semi-solid copper strip continues to move towards the end of the continuous casting process. At this time, the continuous casting traction speed is determined. After spreading the In2O3 particles, the In2O3 particles move with the semi-solid copper strip and are in a relatively stationary state with the semi-solid copper strip. Then, it is only necessary to adjust the distance between the silver molten liquid casting point and the In2O3 spreading point to achieve the goal that the In2O3 particles move with the semi-solid copper strip for a certain period of time after being spread to reach the silver molten liquid casting point for silver molten liquid casting. For example, in this embodiment, it is determined that the In2O3 particles move with the semi-solid copper strip for 20s after being spread. Once the silver molten liquid reaches the casting point, the continuous casting traction speed and the movement time are determined. Multiplying the continuous casting traction speed by the movement time yields the distance between the silver molten liquid casting point and the In2O3 particle spreading point. By moving the silver molten liquid casting point (which can be moved using conventional slide rails or wheels to adjust the distance between the silver molten liquid casting point and the In2O3 particle spreading point), and ensuring that the distance between the silver molten liquid casting point and the In2O3 spreading point matches the calculated result, silver molten liquid casting begins 20 seconds after the In2O3 particles are spread.

[0046] (3) At a casting temperature of 1000℃, molten silver is poured onto a semi-solid copper strip at a flow rate of 2.0 kg / min. As the semi-solid copper strip moves toward the end of the continuous casting process, molten silver is continuously poured to form a silver layer, resulting in a composite strip billet.

[0047] (4) After completing the preparation of a batch of composite strip blanks, hot rolling of this batch of composite strip blanks is carried out at 650℃, with a single-pass deformation of 10%. After completing one hot rolling, the composite strip blanks are annealed at 550℃ for 2 hours. Then, hot rolling and annealing are carried out again. This cycle is repeated until the total deformation of hot rolling reaches 50%. Finally, the last annealing is carried out to obtain Ag / In2O3 / Cu composite strip.

[0048] Example 2 This embodiment prepares Ag / In2O3 / Cu composite tape using the following method: The preparation process in this embodiment was carried out in a nitrogen-protected environment.

[0049] (1) Electrolytic copper with a purity of 99.95% is heated to 1150℃ to form copper molten liquid. The continuous casting traction speed of the continuous casting equipment is set to 5.0m / min, the cooling intensity of the crystallizer is set to 0.5MW / m², and the cooling rate of the secondary cooling zone is set to 10℃ / s to continuously cast the copper molten liquid, and a semi-solid copper strip with a liquid-solid coexistence state on the surface is obtained. The solid phase in the surface of the semi-solid copper strip is 20%.

[0050] (2) Set the swing frequency of the swing funnel to 15 times / min, and use the swing funnel to spread In2O3 particles with a particle size of 100~600nm on the surface of the semi-solid copper strip in the liquid-solid coexistence state. The amount of In2O3 particles added is 0.01g / cm². Adjust the position of the silver molten liquid casting point so that the silver molten liquid is cast 5s after the In2O3 particles are spread.

[0051] (3) At a casting temperature of 980℃, molten silver is poured onto the semi-solid copper strip. The flow rate of the molten silver is 0.05 kg / min. As the semi-solid copper strip moves towards the end of the continuous casting process, the molten silver continues to be poured to form a silver layer, resulting in a composite strip billet. (4) After completing the preparation of a batch of composite strip blanks, hot rolling of the batch of composite strip blanks is carried out at 550℃, with a single-pass deformation of 5%. After completing one hot rolling, the composite strip blanks are annealed at 450℃ for 0.5h. Then hot rolling and annealing are carried out again, and the cycle is repeated until the total deformation of hot rolling reaches 20%. Finally, the Ag / In2O3 / Cu composite strip is obtained after the last annealing.

[0052] Example 3 This embodiment prepares Ag / In2O3 / Cu composite tape using the following method: The preparation process in this embodiment was carried out in a protective environment of argon and nitrogen mixed gas.

[0053] (1) Electrolytic copper with a purity of 99.95% is heated to 1250℃ to form copper molten liquid. The continuous casting traction speed of the continuous casting equipment is set to 0.5m / min, the cooling intensity of the crystallizer is set to 3.0MW / m², and the cooling rate of the secondary cooling zone is set to 100℃ / s to continuously cast the copper molten liquid, and a semi-solid copper strip with a liquid-solid coexistence state on the surface is obtained. The solid phase in the surface of the semi-solid copper strip is 60%.

[0054] (2) Set the oscillation frequency of the oscillating funnel to 60 times / min, and use the oscillating funnel to sprinkle In2O3 particles with a particle size of 50~800nm ​​onto the surface of the semi-solid copper strip in a liquid-solid coexistence state. The amount of In2O3 particles added is 0.50g / cm². Adjust the position of the silver molten liquid casting point so that the silver molten liquid is cast 30s after the In2O3 particles are sprinkled.

[0055] (3) At a casting temperature of 1050℃, molten silver was poured onto the semi-solid copper strip. The flow rate of the molten silver was 5.0 kg / min. As the semi-solid copper strip moved towards the end of the continuous casting process, the molten silver continued to be poured to form a silver layer, resulting in a composite strip billet. (4) After completing the preparation of a batch of composite strip blanks, hot rolling of this batch of composite strip blanks is carried out at 700℃, with a single-pass deformation of 20%. After completing one hot rolling, the composite strip blanks are annealed at 650℃ for 4 hours. Then, hot rolling and annealing are carried out again. This cycle is repeated until the total deformation of hot rolling reaches 80%. Finally, the last annealing is carried out to obtain Ag / In2O3 / Cu composite strip.

[0056] Example 4 This embodiment prepares Ag / In2O3 / Cu composite tape using the following method: The preparation process in this embodiment was carried out in an argon-protected environment.

[0057] (1) Electrolytic copper with a purity of 99.95% is heated to 1200℃ to form copper molten liquid. The continuous casting traction speed of the continuous casting equipment is set to 2.0 m / min, the cooling intensity of the crystallizer is set to 1.8MW / m², and the cooling rate of the secondary cooling zone is set to 50℃ / s to continuously cast the copper molten liquid, and a semi-solid copper strip with a liquid-solid coexistence state on the surface is obtained. The solid phase in the surface of the semi-solid copper strip is 40%.

[0058] (2) Set the oscillation frequency of the oscillating funnel to 30 times / min, and use the oscillating funnel to sprinkle In2O3 particles with a particle size of 100~300nm onto the surface of the semi-solid copper strip in a liquid-solid coexistence state. The amount of In2O3 particles added is 0.08g / cm². Adjust the position of the silver molten liquid casting point so that the silver molten liquid is cast 20s after the In2O3 particles are sprinkled.

[0059] (3) At a casting temperature of 1000℃, molten silver is poured onto the semi-solid copper strip. The flow rate of molten silver is 0.50 kg / min. As the semi-solid copper strip moves toward the end of the continuous casting process, molten silver is continuously poured to form a silver layer, resulting in a composite strip billet.

[0060] (4) After completing the preparation of a batch of composite strip blanks, hot rolling of this batch of composite strip blanks is carried out at 650℃, with a single-pass deformation of 8%. After completing one hot rolling, the composite strip blanks are annealed at 500℃ for 1 hour. Then, hot rolling and annealing are carried out again. This cycle is repeated until the total hot rolling deformation reaches 35%. Finally, the last annealing is carried out to obtain Ag / In2O3 / Cu composite strip.

[0061] Example 5 This embodiment prepares Ag / In2O3 / Cu composite tape using the following method: The preparation process in this embodiment was carried out in an argon-protected environment.

[0062] (1) Electrolytic copper with a purity of 99.95% is heated to 1220℃ to form copper molten liquid. The continuous casting traction speed of the continuous casting equipment is set to 2.0m / min, the cooling intensity of the crystallizer is set to 1.8MW / m², and the cooling rate of the secondary cooling zone is set to 50℃ / s to continuously cast the copper molten liquid, and a semi-solid copper strip with a liquid-solid coexistence state on the surface is obtained. The solid phase in the surface of the semi-solid copper strip is 40%.

[0063] (2) Set the oscillation frequency of the oscillating funnel to 30 times / min, and use the oscillating funnel to sprinkle In2O3 particles with a particle size of 100~300nm onto the surface of the semi-solid copper strip in a liquid-solid coexistence state. The amount of In2O3 particles added is 0.30g / cm². Adjust the position of the silver molten liquid casting point so that the silver molten liquid is cast 20s after the In2O3 particles are sprinkled.

[0064] (3) At a casting temperature of 1000℃, molten silver is poured onto a semi-solid copper strip. The flow rate of molten silver is 3.0 kg / min. As the semi-solid copper strip moves toward the end of the continuous casting process, molten silver is continuously poured to form a silver layer, resulting in a composite strip billet.

[0065] (4) After completing the preparation of a batch of composite strip blanks, hot rolling of this batch of composite strip blanks is carried out at 650℃, with a single-pass deformation of 15%. After completing one hot rolling, the composite strip blanks are annealed at 550℃ for 2 hours. Then, hot rolling and annealing are carried out again. This cycle is repeated until the total hot rolling deformation reaches 75%. Finally, the last annealing is carried out to obtain Ag / In2O3 / Cu composite strip.

[0066] The resistivity of the Ag / In₂O₃ / Cu composite tapes prepared in the embodiments of the present invention was tested using the four-probe method. The results showed that the resistivity of the Ag / In₂O₃ / Cu composite tape in Example 1 was in the range of 1.92–2.05 μΩ·cm, the resistivity of the Ag / In₂O₃ / Cu composite tape in Example 2 was in the range of 2.38–2.56 μΩ·cm, the resistivity of the Ag / In₂O₃ / Cu composite tape in Example 3 was in the range of 2.21–2.37 μΩ·cm, the resistivity of the Ag / In₂O₃ / Cu composite tape in Example 4 was in the range of 1.98–2.12 μΩ·cm, and the resistivity of the Ag / In₂O₃ / Cu composite tape in Example 5 was in the range of 2.03–2.18 μΩ·cm.

[0067] The density of the Ag / In2O3 / Cu composite strip prepared in the embodiments of the present invention was tested using the Archimedes water displacement method.

[0068] The results showed that the overall density of the Ag / In2O3 / Cu composite strip in Example 1 reached 99.4%, the overall density of the Ag / In2O3 / Cu composite strip in Example 2 reached 97.2%, the overall density of the Ag / In2O3 / Cu composite strip in Example 3 reached 98.6%, the overall density of the Ag / In2O3 / Cu composite strip in Example 4 reached 99.1%, and the overall density of the Ag / In2O3 / Cu composite strip in Example 5 reached 99.0%.

[0069] The interfacial bonding performance of the composite strips was evaluated using an interfacial shear test. The results showed that the interfacial bonding strength of the Ag / In2O3 / Cu composite strip in Example 1 reached 152 MPa, the interfacial bonding strength of the Ag / In2O3 / Cu composite strip in Example 2 reached 102 MPa, the interfacial bonding strength of the Ag / In2O3 / Cu composite strip in Example 3 reached 145 MPa, the interfacial bonding strength of the Ag / In2O3 / Cu composite strip in Example 4 reached 148 MPa, and the interfacial bonding strength of the Ag / In2O3 / Cu composite strip in Example 5 reached 161 MPa. The Ag / In2O3 / Cu composite strips prepared by this invention have excellent interfacial bonding stability.

[0070] Through high-temperature wetting experiments, in Example 1, the apparent wetting angle of the Ag liquid in the interface region was 58~72°.

[0071] The contact resistance of the composite strip was tested using a DC micro-ohmmeter.

[0072] The results showed that the contact resistance of Example 1 was 0.18~0.24mΩ; the contact resistance of Example 2 was 0.25~0.31mΩ; the contact resistance of Example 3 was 0.20~0.28mΩ; the contact resistance of Example 4 was 0.19~0.25mΩ; and the contact resistance of Example 5 was 0.17~0.23mΩ.

[0073] The ablation resistance of the composite strip was evaluated using a simulated electric arc ablation test. The test conditions were: current 20A, voltage 24V, switching frequency 1Hz, and 10,000 cycles.

[0074] The results showed that the mass loss was 1.9 mg in Example 1, 3.6 mg in Example 2, 2.4 mg in Example 3, 2.1 mg in Example 4, and 1.8 mg in Example 5.

[0075] This demonstrates that the interface transition layer constructed by the present invention can effectively improve the material's resistance to arc ablation.

[0076] Comparative Example 1 This comparative example uses the same process as Example 1 to prepare the composite tape, the difference being that In2O3 particles are not added in this comparative example.

[0077] In the composite strip of this comparative example, there are many local unbonded areas and interfacial pore defects in the Ag / Cu interface region. The porosity of the interface region reaches 4.5%~7%, the interfacial bonding strength is only 45~60MPa, and the apparent wetting angle of Ag liquid on Cu surface is 92~105°. Compared with Example 1, the wetting and spreading ability of the interface is significantly reduced.

[0078] A comparison of Comparative Example 1 and Example 1 shows that without In2O3 particles for interface regulation, Ag liquid is difficult to form a stable and continuous spread on the Cu surface, resulting in a decrease in the continuous metallurgical bonding ability of the interface and easy formation of interface pores and local unbonded defects.

[0079] Comparative Example 2 This comparative example uses the same process as Example 1 to prepare composite strip, the difference being that this comparative example does not undergo hot rolling and annealing treatment.

[0080] In the composite strip of this comparative example, the porosity increased by 3.8% to 5.2%, the interfacial density decreased significantly, the interfacial bonding strength between the Ag layer and the Cu layer decreased to 30 MPa to 40 MPa, and at the same time, there was local micropore aggregation in the interfacial region, and the continuity of Ag / Cu interfacial contact decreased.

[0081] By comparing Comparative Example 2 with Example 1, it can be seen that the hot rolling and annealing process can further compact the pores in the interface region and promote the diffusion metallurgical bonding of Ag and Cu interface regions, thereby improving the stability of interface bonding and the continuity of the microstructure.

[0082] Comparative Example 3 This comparative example uses a traditional powder metallurgy + rolling composite process to prepare composite strip.

[0083] In this comparative example, Ag powder, Cu powder and In2O3 particles were first uniformly mixed and then pressed into shape, and then sintered and rolled to obtain composite strip.

[0084] The composite strip in this comparative example has obvious residual pores, poor interface structure uniformity, and it is difficult to form a stable and continuous interface transition layer in the interface region. The interfacial bonding strength between the Ag layer and the Cu layer is only 22MPa to 30MPa, and the overall resistivity of the material increases to 2.62μΩ·cm to 2.82μΩ·cm.

[0085] As can be seen from the comparison between this comparative example and Example 1, the present invention adopts a synergistic process of "semi-solid interface in-situ embedding + continuous silver liquid metallurgical bonding + hot rolling plastic densification", which can realize continuous metallurgical bonding and uniform interface structure in the interface region, and has the advantages of continuous process, high production efficiency and suitability for long-size continuous preparation.

[0086] Comparative Example 4 This comparative example uses the same process as Example 1 to prepare the composite strip, the difference being that: In this comparative example, In2O3 particles are sprinkled onto the surface of a completely solid copper strip.

[0087] In this comparative example, In2O3 particles were difficult to stably embed into the copper strip surface, and obvious particle segregation, local detachment, and particle accumulation were observed in the interface region. At the same time, local unbonded areas and interface defects appeared in the Ag / Cu interface region, the porosity of the interface region increased to 5.0%–7.8%, and the interfacial bonding strength between the Ag layer and the Cu layer decreased to 40 MPa–55 MPa.

[0088] As can be seen from this comparative example, the liquid phase coating capability and solid phase skeleton support of the semi-solid liquid-solid coexistence interface of the present invention are conducive to the stable in-situ embedding of In2O3 particles and interface fixation, which is an important condition for the formation of a stable interface transition layer.

[0089] Comparative Example 5 This comparative example uses the same process as Example 1 to prepare composite strips, the difference being that this comparative example uses a continuous coating method to coat a continuous In2O3 coating on the surface of a solid copper strip.

[0090] Although the continuous oxide interface layer in this comparative example can improve the interface wetting behavior to some extent, a continuous brittle layer is easily formed in the interface region. At the same time, the overall resistivity of the material increases to 2.72 μΩ·cm to 2.98 μΩ·cm, the continuity of the interface conductivity decreases significantly, and the interfacial bonding strength between the Ag layer and the Cu layer is 50 MPa to 70 MPa.

[0091] As can be seen from the comparison example, which is the same as Example 1, the interfacial transition layer containing discontinuously dispersed In2O3 particles constructed in this invention can improve the Ag / Cu interfacial bonding ability while avoiding the significant adverse effects of continuous oxide interfacial layers on conductivity.

[0092] The microstructure of the interface region of the Ag / In2O3 / Cu composite strip prepared in this invention was observed, and the results are as follows: Figure 2 As shown.

[0093] pass Figure 2 As can be seen, in the composite strip of the present invention, the interface transition layer containing In2O3 particles can be stably distributed in the Ag / Cu interface region, the interface region has no obvious penetrating pores and delamination defects, and the interface structure is continuous and dense.

[0094] Meanwhile, after In2O3 particles are embedded in the surface of the semi-solid copper strip, they can improve the interface roughness and interface free energy, forming microscale wetting channels that are conducive to the spreading of silver liquid; the liquid copper around the particles forms a local coating structure, which can reduce the contact angle of silver liquid on the copper surface and promote continuous spreading.

[0095] In summary, this invention utilizes the liquid-solid coexistence state of the semi-solid copper strip surface to construct an interfacial transition layer containing discontinuously dispersed In2O3 particles. Combined with continuous silver melt casting and hot rolling annealing, this effectively improves the wettability of Ag liquid on the Cu surface, enhancing the interfacial bonding strength, microstructure density, and electrical stability of the composite strip. The composite strip of this invention achieves a high level of interfacial bonding strength, reduces interfacial porosity to a low level, and maintains a low resistivity level, demonstrating excellent application prospects for highly reliable conductive connections in low-voltage electrical appliances, electrical contact components, rail transportation, and new energy power transmission and distribution.

[0096] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the essence and scope of the technical solutions of the present invention.

Claims

1. A continuous metallurgical composite method for Ag / In₂O₃ / Cu composite strips based on semi-solid interface regulation, characterized in that: The continuous metallurgical composite method for Ag / In2O3 / Cu composite strip includes the following steps: S1: Continuous casting of molten copper yields a semi-solid copper strip with a liquid-solid coexistence state on the surface. S2: Spread In2O3 particles on the surface of the semi-solid copper strip in the liquid-solid coexistence state in step S1. Under the action of capillary force and interfacial tension at the liquid-solid coexistence interface, the In2O3 particles are embedded in situ into the surface of the semi-solid copper strip to form an interfacial transition layer containing In2O3 particles. S3: Cast molten silver onto the interface transition layer of step S2 to obtain a composite strip blank; S4: Perform multiple hot rolling and annealing cycles on the composite strip blank obtained in step S3 to obtain Ag / In2O3 / Cu composite strip.

2. The continuous metallurgical composite method for Ag / In₂O₃ / Cu composite strips according to claim 1, characterized in that: In step S1, the cooling intensity of the crystallizer during the continuous casting process is 0.5~3.0 MW / m. 2 The continuous casting traction speed is 0.5–5.0 m / min, and the cooling rate in the secondary cooling zone is 10–100 °C / s.

3. The continuous metallurgical composite method for Ag / In₂O₃ / Cu composite strips according to claim 1, characterized in that: In step S1, the casting temperature of the molten copper is 1150~1250℃.

4. The continuous metallurgical composite method for Ag / In₂O₃ / Cu composite strips according to claim 1, characterized in that: In step S2, In2O3 particles are evenly distributed on the surface of the semi-solid copper strip, at a concentration of 0.01~0.50 g / cm³ based on the area of ​​the semi-solid copper strip. 2 In2O3 particles are evenly distributed on the surface of the semi-solid copper strip in a liquid-solid coexistence state.

5. The continuous metallurgical composite method for Ag / In₂O₃ / Cu composite strips according to claim 1, characterized in that: In step S2, the In2O3 particles have a particle size of 50~800nm.

6. The continuous metallurgical composite method for Ag / In₂O₃ / Cu composite strip according to claim 1, characterized in that: In step S3, after the In2O3 particles are sprinkled, they travel with the semi-solid copper strip for 5-30 seconds and then enter the silver molten liquid casting area to begin silver molten liquid casting.

7. The continuous metallurgical composite method for Ag / In₂O₃ / Cu composite strip according to claim 1, characterized in that: In step S3, the casting temperature of the molten silver is 980~1050℃.

8. The continuous metallurgical composite method for Ag / In₂O₃ / Cu composite strip according to claim 1, characterized in that: In step S3, the flow rate of the silver molten liquid casting is 0.05–5 kg / min.

9. The continuous metallurgical composite method for Ag / In₂O₃ / Cu composite strips according to claim 1, characterized in that: In step S4, the hot rolling temperature is 550–700℃, the single-pass hot rolling deformation is 5%–20%, and the total hot rolling deformation is 20%–80%; the annealing temperature is 450–650℃, and the single annealing holding time is 0.5–4h.

10. The continuous metallurgical composite method for Ag / In₂O₃ / Cu composite strips according to any one of claims 1-9, characterized in that: Steps S1, S2, S3, and S4 are all performed under inert gas protection conditions, wherein the inert gas is argon, nitrogen, or a mixture of argon and nitrogen.